The function is y =
![(1)/(3)^(x)](https://img.qammunity.org/2019/formulas/mathematics/college/6rotc1vwekxbvm5b5ubacknj1iysunm8m4.png)
This can be found by using the base equation for exponential y =
. Now we can use the second ordered pair (0, 1) to find the value of a.
y =
![ab^(x)](https://img.qammunity.org/2019/formulas/mathematics/college/nst79oqb7nr5bvxpwqgh99vtfcr5q67f6z.png)
1 =
![ab^(0)](https://img.qammunity.org/2019/formulas/mathematics/college/997p9m2lyqic8zob8k3akp78l535delas4.png)
1 = a(1)
1 = a
Now that we have a, we can solve for b using any other ordered pair.
y =
![ab^(x)](https://img.qammunity.org/2019/formulas/mathematics/college/nst79oqb7nr5bvxpwqgh99vtfcr5q67f6z.png)
=
![(1)b^(1)](https://img.qammunity.org/2019/formulas/mathematics/college/95d2xcv7x9rbzruzt8a7x0rg27w6u5cwk4.png)
= (1)(b)
= b
Now we can use these in the same equation.
y =
![(1)/(3)^(x)](https://img.qammunity.org/2019/formulas/mathematics/college/6rotc1vwekxbvm5b5ubacknj1iysunm8m4.png)